A new green-flowered Aa (Cranichideae) from Peru - Trujillo, Delsy; Edquén, José D.; Fernandez-Hilario, Robin; Wong Sato, Akira A.; Salazar, Gerardo A. (Lankesteriana: International Journal on Orchidology, 2024)
A new species from the Peruvian Andes, Aa olivacea, is described and illustrated. Information concerning distribution, habitat, ecology, and conservation status is provided. The new species is similar to A. hieronymi by its dense spikes of dark green and brown flowers with translucent whitish floral bracts; but differs from it by its elliptic to lanceolate leaves, 60 to 100-flowered spikes, glabrous rachis, lateral sepals with the margin entire to occasionally minutely erose near the apex, petals with slightly erose to sinuate apical margin, lip unlobed with lacerate to erose margin, and ovary with scarce hairs. Furthermore, A. tenebrosa is proposed as a synonym of A. hieronymi, A. nigrescens is recognized as a distinct species from A. leucantha, and A. lehmannii is confirmed to be an illegitimate, superfluous name for A. leucantha.